Hello Music Lady: Have You Brought A New Instrument Today? A Music Therapy Group for Children of Families in the UK Armed Forces. - White, Becky (Voices: A World Forum for Music Therapy, 2010)
The paper describes a music therapy group that took place in a UK primary school on an armed forces base. The school described is the only state school in the UK for families in the armed forces. The families staying on the base are in transition for reasons such as, family break-up, domestic problems, leaving the forces, emergency evacuation from overseas, and transition between postings. This paper traces how the group evolved over eleven months. It focuses on the practical considerations required when setting up a music therapy group. It describes the thought processes I went through in doing this work, and looks at how the work was integrated into the school. It considers the setting up of the group, providing a framework, working with staff, structuring the sessions, and how the group ended.